Regional development project management: financial aspect - Agres, Oksana; Sodoma, Ruslana; Ilchyshyn, Igor; Kovalchuk, Oleg; Shmatkovska, Tetiana (Technology audit and production reserves, 2025)
The article explores the financial aspect of managing regional development projects in the context of strategic planning and socio-economic challenges. Particular attention is paid to project financing, their role in investment incentives for regions, infrastructure modernization and human capital development. The object of the study is practical mechanisms for financing projects aimed at the socio-economic development of regions. The authors analyze the main sources of funding, the role of the State Fund for Regional Development (SFRD), and co-financing mechanisms from local budgets. The authors consider the impact of project financing on regional development, taking into account current economic and social circumstances, including military challenges. Particular attention is paid to the strategic management of financial resources, which allows achieving long-term sustainable development of territories and reducing territorial disparities. The model of regional development project management has been improved, reflecting a systematic and strategic approach to the financial support of regional initiatives, with a focus on efficiency, transparency, multichannel financing, risk management, and institutional capacity, which ensures its adaptability to the challenges of modern regional policy. The proposed approaches can be used as a basis for the development of regional development strategies focused on achieving social justice and economic efficiency. Analyzing the research of scholars, it has been found that most of them focus on the need to attract alternative sources of funding. This will increase the financial capacity of local budgets by 20–30% compared to traditional approaches. Some models of interregional financing adapted to the conditions of Ukraine demonstrate a 25% increase in resource efficiency due to the digitalization of infrastructure project management. The article also emphasizes the importance of cross-sectoral cooperation and partnerships between the public, private and civil society sectors in project financing. The presented results are of practical importance for local governments, think tanks, and regional development policymakers. In the context of European integration processes, the application of the best European practices in financial management at the regional level is becoming increasingly important. The implementation of innovative financial instruments can enhance the adaptability of regional systems to external shocks. The results of the study can serve as an analytical basis for further scientific developments and implementation of effective state regional policy.